(In)equity of exceptional academic achievement in South African higher education - Munro, Nicholas; Vithal, Renuka; Murray, Michael (South African Journal of Higher Education, 2016)
The phenomenon of exceptional academic achievement in South African higher education is under-researched and frequently overshadowed by concerns around failure, underachievement, and poor quality of throughput. This paper reports on a study of exceptional academic achievement in one South African university. Taking a selection of contextually relevant and available variables, a logistic regression methodology was applied to a sample of graduates from the University of KwaZulu-Natal - an internationally ranked, recently merged and rapidly transforming South African university. As an outcome of this application, a model of the socio-demographic and educational variables associated with exceptional academic achievement in undergraduate students was developed. The model suggests that variations in race, gender, financial aid allocation, matriculation score and matriculation English symbol are significantly associated with increased odds of exceptional academic achievement. Interaction terms for race and gender were also entered in the model. The study also found that when compared to all other groups, White females were most likely to excel academically. The results from the study provide a basis for connecting discourses pertaining to excellence, exceptional academic achievement, and quality of throughput at an undergraduate level with those of equity and equality in South African higher education. It highlights that although some advances in the equity of academic achievement for different race and social groups at the University of KwaZulu-Natal have been made, there is considerable room for improvement in this in the domain of exceptional academic achievement.